Cloud computing : theory and practice - Marinescu, Dan C. (Cambridge, MA : Morgan Kaufmann is an imprint of Elsevier, 2023)
"Cloud Computing: Theory and Practice, Third Edition provides students and IT professionals with an in-depth analysis of the cloud from the ground up. After an introduction to network-centric computing and network-centric content, the book reviews basic concepts of concurrency and parallel and distributed systems, presents critical components of the cloud ecosystem as cloud service providers, cloud access, cloud data storage, and cloud hardware and software, covers cloud applications and cloud security, and presents research topics in cloud computing. Specific topics covered include resource virtualization, resource management and scheduling, and advanced topics like the impact of scale on efficiency, cloud scheduling subject to deadlines, alternative cloud architectures, and vehicular clouds. An included glossary covers terms grouped in several categories, from general to services, virtualization, desirable attributes and security." --
1. Introduction 2. The cloud ecosystem 3. Parallel processing and distributed computing 4. Cloud hardware and software 5.Cloud resource virtualization 6. Cloud access and cloud interconnection networks 7.Cloud data storage 8. Cloud security 9. Cloud resource management and scheduling 10. Concurrency and cloud computing 11. Cloud applications 12. Big Data, data streaming, and the mobile cloud 13. Emerging clouds
Includes bibliographical references (pages 597-620) and index.
COECS
In English
Keywords: Cloud computing